Feasibility of UXO detection via pulsed neutron-neutron logging - Köhli, Markus; Schmoldt, Jan-Philipp (Applied radiation and isotopes, 2022)
The technique of pulsed neutron-neutron logging (PNNL) is applied in geosciences and petrol chemistry in order to measure hydrogen sources in downhole oil exploration. 14.1MeV neutrons from a deuterium-tritium fusion source provide also the capabilities for a time-of-flight based approach to identify the fillers of unexploded ordnances (UXO) by characterizing their hydrogen, nitrogen and oxygen contents. Using the Monte-Carlo tool URANOS we find that soil moisture is the key variable for the penetration depth of neutrons into the ground. Later detection windows after the initial pulse are to be preferred over earlier thresholds. Taking exemplarily a 100lb and a 1000lb bomb the range in a typical soil configuration is found to lie between 10cm and 50cm at a soil bulk density of 1.4g/cm3. Yet, other objects like a steel bar can cause similar signatures of signal dampening.